487 The Influence of Inhaled Corticotherapy on the Growth and Development in Asthmatic Children. (October 2012) - Mohor, C; Neamtu, MB; Neamtu, ML
Abstract : Background: Inhaled corticotherapy is the main anti-inflammatory controller type therapy in asthmatic children. Impaired growth as a result of long-term corticotherapy remains a disputed issue of topical interest for both endocrinologists, pneumologists and pediatricians. Objective: The study evaluates the influence of long term small dose inhaled corticotherapy on growth and somatic development in asthmatic children. Methods: Observational analytical study on 2 samples of subjects. The study group: 100 asthmatic children with small dose inhaled corticotherapy (beclomethasone dipropionate Becotide 200–400 µg/day or fluticasone propionate Flixotide 100–300 µg/day), for 24 months therapy. The control group: 100 healthy children. Both groups were divided in 5 homogeneous age subgroups, between 5–19 years of age. For both groups the relevant anthropometric landmarks for assessing growth were measured in dynamics at every 6 months, in a 2 years follow-up: body height, shank and plant length growth; thorax, skull, hip, shank and arm circumference growth. The statistical SPSS software was utilized and the index t-test was calculated (p>0.84). Results: Comparative evaluation of anthropometric indices after 1 year, respectively 2 years of medication in all age subgroups revealed a minimum reducing of the growth rate in the study group without statistical significance. Conclusions: Inhaled corticotherapy in small doses in a long term therapy (2 years) doesn't significantly affect growth and somatic development in asthmatic children.